The Poetics of Vulnerability: Diaspora, Race, and Global Citizenship in A.M. Klein’s The Second Scroll and Dionne Brand’s Thirsty - Härting, Heike (Studies in Canadian Literature, 2007)
A critical reading of Michael Hardt and Antonio Negri’s notion of the "multitude" enables the analysis of such affective conditions of global citizenship as diasporic melancholia and mourning, as identified by Ranjana Khanna. By reading the submerged narrative of race in A.M. Klein’s novella The Second Scroll (1951) against Dionne Brand’s particular employment of metaphor in her long poem Thirsty (2002), it is possible to anchor global citizenship in a diasporic poetics of differential vulnerability that links disparate texts of national mourning and remains attentive to the cultural work performed by and on the body. In this way global citizenship becomes thinkable both through its complicity with the racialized histories of the present and as a transformative, sensuous practice committed to reshaping communal relationships.